1193 Night-shifts, dna methylation and telomere length: preliminary results from a survey on a sample of italian nurses. (24th April 2018) - Carugno, M; Crespi, E; Bollati, V; Tarantini, L; Dioni, L; Consonni, D; Maggioni, C; Costa, G; Pesatori, AC
Abstract : Introduction: IARC defined shift work as probably carcinogenic to humans (Group 2A), after investigations highlighted an increased breast cancer risk in night-shift female workers. The biological mechanisms underlying this association are still unclear. Hence, we evaluated the relationship between night-shift work and molecular alterations potentially related to increased cancer risk, in detail: DNA methylation of the oestrogen receptor gene (ER-Beta) and tumour suppressor genes (BRCA1, p53, p16), global DNA methylation estimated in repeated elements (LINE-1, Alu) and telomere length (TL). Methods: 46 female nurses (age: 35–45 years) who had been working in night-shifts for at least two years (length of service ≥five years) were recruited at the Policlinico Hospital (Milan, Italy) and matched for age, sex and length of service to 51 colleagues not working in night-shifts. Each subject was administered a structured questionnaire and withdrawn a 12 mL blood sample. Linear regression models adjusted for age, BMI, parity, smoking habit and oral contraceptive use were then applied. Results: Working in night-shifts (yes/no) was associated with BRCA1 hypomethylation (β: −0.512, 95% CI: −1.039 to 0.015). When considering also former night-shift workers, the number of years in night-shifts (NYNS) was associated with hypomethylation of BRCA1 (β: −0.084, 95% CI: −0.127 to −0.042), p53 (β: −0.072, 95% CI: −0.133 to −0.011) and LINE-1 (β: −0.043, 95% CI: −0.083 to −0.002). After graphically inspecting the NYNS-TL relationship, we stratified our study population by NYNS <15 vs ≥15 years. Among nurses with NYNS ≥15 years, NYNS was associated with telomere shortening (β: −0.065, 95% CI: −0.122 to −0.008) and hypermethylation of BRCA1, p53 and LINE-1. Conclusion: Our results show epigenetic alterations that might play a role in cellular ageing, genomic instability and carcinogenesis. We are currently extending our study to other molecular targets involved in the cascade of events that might bring from night-shift exposure to cancer.